Evaporation of binary nanofluid droplet - Kwa, Zheng Yu (2018)
This paper investigates the changes in the initial wettability, evaporation rate and deposition patterns of an evaporating ethanol-water droplet with suspended graphite nanoparticles by varying the ethanol and graphite nanoparticle concentrations. Concentration of the ethanol ranged from 0% to 40% and the graphite nanoparticles ranged from 0.1g/L to 5g/L. The experiment was conducted on a silicon wafer, results being measured by a top view microscope and a side view high speed camera. Measurements from the experiments showed that the ethanol concentration affects the initial wettability, evaporation rate and deposition pattern, while the graphite nanoparticle concentration affects the initial wettability and deposition pattern. These findings help to contribute to the deeper understanding between the interaction of ethanol and graphite nanoparticle in the hydrodynamics and deposition patterns of the evaporating ethanol-water droplet with suspended graphite nanoparticles.